Records management system with sms notification for smart clean laundry / Fauziah Mohamad Yusof - Mohamad Yusof, Fauziah (2017)
Smart Clean Laundry is a shop that provides various types of laundry services such as wash and dry, dry cleaning, iron and also carpet cleaning. Up until now, they still using manual method in their daily business. All of customer record and transaction is stored in the receipt book. Because of that, they are having difficulty especially when they want to view the records. Besides that, there is no reference for staff to view customer’s pickup date so they overlook customers who are late. Thus, Records Management System with SMS Notification for Smart Clean Laundry; a web based system is developed to help them to manage customer transaction records in more organized way, easy to retrieve and minimize the problems occurred in their current business process. This project focused on customer management such as their information, laundry, pickup date and payment. Besides that, a dashboard calendar is implemented into the system for the staff to view customer’s pickup date and SMS reminder also can be send to the customers through the system. This project is carried out with the aim to develop web based records management system with SMS notification for Smart Clean Laundry. This project use three-tier architecture and SDLC as a methodology to develop the system. As a result, a fully functional web based records management system with SMS notification is produced together with documentations of Software Requirements Specification (SRS) and Software Design Document (SDD). In the future work, this system can become more advanced by make it into an online system that can also be used by the customers.